Current Trends and Challenges in Laboratory Investigation of the Covid-19 Pandemic (Medico Legal Update, 2020)
The ongoing virus impact in the whole world is COVID19 infection has led to unprecedented crisis pavingto outrage of the world citizens. The highly contagious virus started its spread from the China during themonth of late November 2019 and spread to all over the world. The COVID-19 pandemic led catastrophe andearlier episodes of similar epidemic SARS outbreaks in China and Middle East interrogate the preparednessin handling such predicament. The major symptomatic manifestations of patients are not so accurate andvary from one person to another and higher frequency of asymptomatic cases often misled diagnosis,unless the CT chest scan findings affirms the disease progress into fatal SARS. Disambiguation over theother viral respiratory illnesses similar to COVID-19 needs to be meticulously handled by emphasize onsimultaneous co-detection of multiple viral pathogens. Henceforth, robust diagnostic tools are necessitatedto substantiate suspected cases and to screen large population in less time. This review would keenly focuson the challenging prime requisite for accurate laboratory testing of the infection and the potentials ofvarious techniques in investigating the pandemic.